2004
DOI: 10.1590/s1413-70542004000100014
|View full text |Cite
|
Sign up to set email alerts
|

Influência de sanificantes nas características microbiológicas, físicas e físico-químicas de cebola (Allium cepa L.) minimamente processada

Abstract: RESUMOObjetivou-se com esta pesquisa avaliar a influência dos sanificantes peróxido de hidrogênio (H 2 O 2 ) e dicloro isocianurato de sódio (NaDCC) sobre a vida de prateleira da cebola (Allium cepa L.) minimamente processada, com base no desenvolvimento da microbiota e características físicas e físico-químicas. As cebolas foram previamente lavadas, descascadas e fatiadas. Foram testados 6 tratamentos em 3 blocos casualizados. Os tratamentos foram: controle, H 2 O 2 (2%), H 2 O 2 (4%), H 2 O 2 (6%), NaDCC (50p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
(2 reference statements)
0
3
2
2
Order By: Relevance
“…During the senescence period, the concentration of organic acids tends to decrease, due to the possible leakage of cell fluid and volatilization of these acids (Berli et al, 2004). This effect, however, was not observed in lamb's-ear leaves in the present study.…”
Section: Total Titratable Acidity (Tta)contrasting
confidence: 71%
“…During the senescence period, the concentration of organic acids tends to decrease, due to the possible leakage of cell fluid and volatilization of these acids (Berli et al, 2004). This effect, however, was not observed in lamb's-ear leaves in the present study.…”
Section: Total Titratable Acidity (Tta)contrasting
confidence: 71%
“…NaDCC is widely used as a safe disinfection tablet in daily life and industries. Previous research indicated that application of NaDCC at 50 ppm can prolong shelf life of fresh-cut onion with higher pH value and lower titratable acidity [22]. Additionally, NaDCC treatment in combination with gamma irradiation is able to control soft rot disease caused by Rhizopus of sweet potatoes, pears and paprikas after harvest [2325].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble solids represent the concentration of substances dissolved in the cellular content, including vitamins, pectins, phenols, organic acids, pigments, and sugars (Beckles, 2012). Still, according to Beerli et al (2004), the reduction in the soluble solids during storage probably occurs due to the consumption of substrates in the respiratory metabolism, characteristic of catabolic reactions of senescence. °Brix reduction during the storage of onion bulbs corroborates the studies carried out by Melo et al (2012), where, studying the cultivars Beta Cristal and Óptima during 60 days of storage, describe that the levels of soluble solids decreased differently between cultivars during the days of cold storage at 5 °C.…”
Section: Resultsmentioning
confidence: 99%